Rekonstruksi Konsep Wakaf Produktif dalam Perspektif Ekonomi Islam - Abdul Hamid; Udin Komarudin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Waqf is an Islamic philanthropic instrument with significant potential to support economic development and social welfare. However, waqf practices in many Muslim countries, including Indonesia, are still predominantly managed in a traditional and consumptive manner, resulting in limited economic impact. This article aims to reconstruct the concept of productive waqf from the perspective of Islamic economics by emphasizing the maq??id al-shar?‘ah framework. This study employs a library research method by analyzing classical and contemporary literature, including reputable international journals, academic books, and relevant regulations on waqf. The findings indicate that productive waqf has a strong normative foundation in Islam and plays a strategic role as an instrument for wealth redistribution and sustainable economic development. The reconstruction of productive waqf requires a paradigm shift toward professional waqf management, good governance practices, and integration with modern Islamic financial instruments. This study contributes theoretically to the development of Islamic economics and provides practical implications for strengthening productive waqf management in response to contemporary economic challenges.